The Japanese Labour Market during the Global Financial Crisis and the Role of Non-Standard Work: A Micro Perspective - Alexander Hijzen; Ryo Kambayashi; Hiroshi Teruyama; Yuji Genda (Institute for the Study of Labor (IZA), 2015)
This paper analyses aggregate labour dynamics during the global financial crisis in Japan and the role of nonstandard work using micro data. The analysis proceeds in two steps. First, using comprehensive establishment-level datasets for the period 1991-2009, it provides a detailed portrait of the adjustment behaviour of establishments at the micro level. Second, it compares aggregate labour market dynamics during the global financial crisis with that observed during the 1997 crisis and decomposes the observed differences into components that can be attributed to changes in the micro-adjustment behaviour of Japanese establishments, changes in the incidence of non-standard work and changes in the distribution of shocks across establishments. It finds that the incidence of non-standard work has increased considerably, worker turnover is much higher among non-standard than standard workers and adjustments in working-time are less important for non-standard workers. Counterfactual simulations suggest that the employment response during the global crisis would have been smaller if the incidence of non-standard work remained at the level observed during the 1997 crisis. The relatively small employment response observed during the global financial crisis is therefore driven by factors others than the increase in the incidence of non-standard work.
Keywords: D22; E24; J23; J41; 330; job quality; labour market resilience; labour market duality; temporary work; crisis